2022
DOI: 10.3389/fpsyg.2022.850479
|View full text |Cite
|
Sign up to set email alerts
|

Development and Reliability and Validity Test to the Parenting Stress Questionnaire for Two-Child Mothers

Abstract: China is getting old before it gets rich. Among women of childbearing age, there seems to be little interest in having multiple children, and parenting stress may be one of the reasons. There are differences in the parenting stress felt by mothers with one child and those with two, but there is no questionnaire specifically aimed at the parenting stress felt by mothers of multiples in China. The purpose of the present study is to develop and verify a questionnaire specifically aimed at measuring the stress of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…And the studies implied that disproportionate burden of household duties, lack of leadership opportunities, lack of support during maternity leave and lactation had tremendous effect on female physicians’ experience with job satisfaction and burnout ( Jia et al, 2013 ; Yeluru et al, 2022 ). In the past decades, family planning policy in China has undergone gradual adjustment, from one-child policy to two-child policy for couples who were both one-child, to two-child policy for all couples, and to three-child policy for all couples ( Zhang et al, 2022 ). Under the three-child family planning policy, statutory paid maternity leave and fair promotion opportunities might improve job satisfaction and performance and reduce turnover of women workers, especially for female nurses.…”
Section: Discussionmentioning
confidence: 99%
“…And the studies implied that disproportionate burden of household duties, lack of leadership opportunities, lack of support during maternity leave and lactation had tremendous effect on female physicians’ experience with job satisfaction and burnout ( Jia et al, 2013 ; Yeluru et al, 2022 ). In the past decades, family planning policy in China has undergone gradual adjustment, from one-child policy to two-child policy for couples who were both one-child, to two-child policy for all couples, and to three-child policy for all couples ( Zhang et al, 2022 ). Under the three-child family planning policy, statutory paid maternity leave and fair promotion opportunities might improve job satisfaction and performance and reduce turnover of women workers, especially for female nurses.…”
Section: Discussionmentioning
confidence: 99%
“…More and more mothers of young children enter the labor force, and families face challenges regarding the balance between parenting and work [3,4]. Traditional systems of infant and toddler care have been weakened, and members of the "sandwich generation" who need to take care of old people and young children shoulder an increased burden of responsibility for care [5][6][7]. The care of young children under 3 years old in China has traditionally been undertaken within the family; external sources of family support for infant and toddler care are particularly scarce [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The care of young children under 3 years old in China has traditionally been undertaken within the family; external sources of family support for infant and toddler care are particularly scarce [8,9]. Since the enactment of the two-child policy and the newly enacted threechild policy in mainland China [7,10], the traditional mother-dominated childcare model cannot be sustained, and the problem of caring for children under 3 years old needs to be solved urgently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents may experience negative emotions such as unease, fear, worry, and anxiety during parenthood due to their own problems, parent-child relationships, the family environment, and other factors (1,2). It has been reported that fathers may also develop negative feelings and fear even during the perinatal period (3).…”
Section: Introductionmentioning
confidence: 99%